Metformin suppresses the proliferation and invasion through NF-kB and MMPs in MCF-7 cell line - Beşli, Nail; Yenmiş, Güven; Tunçdemir, Matem; Saraç, Elif Yaprak; Doğan, Sibel; Solakoğlu, Seyhun; Sultukbey, Gönül Kanigur (Türk Biyokimya Dergisi, 2020)
Özet: Amaç: Bir meme kanseri hücre soyu olan MCF-7, östrojen reseptörü (ER) pozitif meme kanseri ve ER-pozitif tümörlerin farklı sınıflarını temsil eden birçok alt klonun deneyleri için kullanılır. Potansiyel bir anti-kanser ajanı olan metforminin, MCF-7 hücre soyunda hücre çoğalması ve NF-kB (p65), MMP-2 ve MMP-9 ekspresyonları üzerindeki etkisini belirlemeyi amaçladık. Gereç ve Yöntem: MCF-7 hücreleri (insan meme adenokarsinomu) 24 saat boyunca metformin artan dozları (0–50 mM) ile muamele edildi. Metforminin anti-proliferatif etkisi, BrdU proliferasyon deneyi ile incelendi ve NF-kB (p65), MMP-2 ve MMP-9 ekspresyon seviyeleri ise immünositokimyasal boyama ile analiz edildi. Bulgular: Hücre proliferasyonunun yüzdesi, 10 ve 50 mM’lik metformin dozları ile önemli ölçüde azaldı (p?<?0.001). Nükleer NF-kB (p65), MMP-9 ve MMP-2’nin ekspresyon seviyeleri, 50 mM metformin ile muamele edilmiş hücrelerde önemli ölçüde azalırken, sitoplazmik NF-kB’nin (p65) ekspresyonu, kontrol grubuna göre (p?<?0.05) arttı. 10 mM metformin de MMP-9 ekspresyonunu anlamlı şekilde azalttı (p?<?0.05).Sonuç: Metformin, meme kanseri hücrelerinde yüksek oranda eksprese edilen NF-kB(p65) ve MMP-2 ve MMP-9 ekspresyon seviyelerini önemli ölçüde azaltarak, MCF-7 hücrelerinin proliferasyonu, invazyonu ve metastazı üzerinde etkili olabilir.

Abstract: Abstract Objective: MCF-7 cells, a breast cancer cell line, are used for experiments of estrogen receptor (ER)-positive breast cancer and many sub-clones representing different classes of ER-positive tumors. We aimed to determine the efficacy of metformin, a potential anti-cancer agent, on the cell proliferation, and the expressions of NF-kB (p65), MMP-2 and MMP-9 in MCF-7 cell line. Materials and methods: MCF-7 cells (human breast adenocarcinoma) were treated with elevating doses of metformin (0–50 mM) for 24 h. The anti-proliferative effect of metformin was studied by BrdU proliferation assay, and the expression levels of NF-kB (p65), MMP-2 and MMP-9 were analyzed by immunocytochemical staining. Results: The percentage of cell proliferation was reduced significantly by 10 and 50 mM doses of metformin (p?<?0.001). The expression levels of nuclear NF-kB (p65), MMP-9 and MMP-2 were considerably reduced in 50 mM metformin treated cells while the expression of cytoplasmic NF-kB (p65) elevated compared to control group (p?<?0.05). Ten millimolar metformin also reduced expression of MMP-9 significantly (p?<?0.05). Conclusion: Metformin may act on the proliferation, and the processes of invasion and metastasis of MCF-7 cells through blocking NF-kB, which is intensely expressed in breast cancer cells, and through diminishing the expression of MMP-2 and MMP-9 significantly
Keywords: Breast cancer; Matrix metalloproteinase; MCF-7; Metformin; NF-kB; Meme kanseri; Matrix Metalloproteinaz; Metformin